THE EFFECT OF GENDER ON BOARD, FINANCIAL EXPERTISE OF CEO, AND POLITICAL CONNECTION TOWARD FRAUDULENT FINANCIAL REPORTING IN INDONESIA - Chika Meyora Ismato; Elfina Astrella Sambuaga (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
The view of this study is to examine the effect of gender and expertise and political connection on a fraudulent financial statement. Financial Reporting is measured by managerial ability which presents with M-SCORE variable, gender on board, financial expertise, and political connection. The population used in this study are the countries in Indonesia listed in IDX and S&P Capital IQ for 2018-2021. In this study, a total of 100 industrial enterprises whose annual reports were made public and who disclosed their external auditors on the Indonesia stock exchange were chosen on purpose. STATA 17 is used to test the sample in this study using the multiple regression method. The study in this study shows the following result: the impact of gender on board towards fraudulent financial statements is significant, and the impact of political connection towards fraudulent financial statements is insignificant. Also, financial expertise towards fraudulent financial statements can’t be defined.